Deposit insurance, bank ownership and depositor behavior - Sümeyra Atmaca; Karolin Kirschenmann; Steven Ongena; Koen Schoors (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We employ proprietary data from a large bank to analyze how - in times of crisis - depositors react to a bank nationalization, re-privatization and an accompanying increase in deposit insurance. Nationalization slows depositors fleeing the bank, provided they have sufficient trust in the national government, while the increase in deposit insurance spurs depositors below the new 100K limit to deposit more. Prior to nationalization, depositors bunch just below the then-prevailing 20K limit. But they abandon bunching entirely during state-ownership, to return to bunching below the new 100K limit after re-privatization. Especially depositors with low switching costs are moving money around.
Keywords: G21; G28; H13; N23; 330; deposit insurance; coverage limit; bank nationalization; depositor heterogeneity